Knowledge Regarding Computer Ergonomics and Incidence of Musculoskeletal Disorders among Desktop Users - Kanika; Bindu Joseph; Jimmy Dharwal (Indian Journal of Forensic Medicine & Toxicology, 2021)
The use of computers has become universal. Computer technology plays an integral role in our personal,professional and educational lives and neglecting the principles of ergonomics during computer utility raisesthe risk of health problems. Musculoskeletal disorders (MSDs), Visual symptoms and Insomnia are thecommon health problems among desktop users. Aims and Objectives: To assess the knowledge regardingcomputer ergonomics and incidence of musculoskeletal disorders Methodology: In this cross-sectionalresearch study 130 desktop users were recruited as study participants. The tool used i.e. selected variablesregarding study participants characteristics and Structured Knowledge questionnaire (35 items) Results:More than 2/3rd of study participants (90%) were reported about discomfort related to eye strain, head andneck, wrist and hand, elbow, upper back, lower back, hips and thighs and knees. Less than half of the studyparticipants were at average level of knowledge related to computer ergonomics and There was significantassociation of selected variables (discomfort and severity of hand and wrist discomfort) was found with theKnowledge of computer ergonomics. Conclusions: Findings of this study concluded that there was majorityof study participants reported discomfort related to the eye strain, head and neck, wrist and hand, elbow,upper back, lower back, hips and thighs and knees and severity of hand and wrist discomfort which showedthat these organs get influence more by desktop based on body configuration.